Identification and antibiotic sensitivity test of isolated aerobic bacteria from acne vulgaris - Lily Suciati; Iman Santoso; Qonita Gina Fadhilah; Sogandi Sogandi (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
Acne vulgaris is an inflammatory skin condition caused by various factors, including bacteria in the sebaceous glands of the dermis. Inflammation in acne vulgaris can lead to the formation of purulent papules, known as acne papulopustulosa. Treatment options for acne vulgaris include topical antibiotics, such as clindamycin, and oral antibiotics, such as tetracycline, minocycline, and doxycycline. This study aimed to isolate and identify aerobic bacteria associated with acne vulgaris and assess their susceptibility to commonly used antibiotics. Aerobic bacteria from the papulopustules of six patients were isolated using the quadrant streak method on Mueller Hinton Agar (MHA) and Mannitol Salt Agar (MSA). Twelve isolates were obtained, characterized using Gram staining, catalase, and oxidase tests, and identified by 16S rRNA sequencing. The most common bacteria were Staphylococcus spp. (five patients), followed by Klebsiella sp. (two patients), Enterobacter sp. (one patient), and Citrobacter sp. (one patient). Sensitivity testing was conducted with tetracycline, minocycline, doxycycline, and clindamycin, following the Clinical Laboratory Standards Institute (CLSI) guidelines. The results showed that the effectiveness of tetracycline was 50.0%, minocycline 58.3%, and doxycycline 58.3%, while all isolates were resistant to clindamycin. Due to the small sample size, the findings should be interpreted as preliminary and descriptive, providing exploratory insight into the diversity of aerobic bacteria in acne lesions and their antibiotic susceptibility.